The Impact of Computational Pharmacology - Matthew N.O. Sadiku; Sheena M. Reeves; Sarhan M. Musa (European Scientific Journal, ESJ, 2019)
Pharmacology is the study of how drugs interact within the human body. The field covers a variety of topics such as pharmaceutical capabilities and interactions. Early studies in pharmacology focused on the effects of natural substances in the body as a means of therapeutic treatment. Modern pharmacology uses computation and modeling as research tools on a cellular level. Computational models are useful in almost every scientific and engineering discipline especially when practical and ethical considerations prevent experimenting with real systems. The models are needed to design various parts of the drug discovery process. Computer programs for designing compounds is one key area of computational pharmacology. Another area of interest are digital repositories for investigating chemical interactions. Modern pharmacology now involves using a computational method. This paper provides a brief introduction to computational pharmacology.